# a2 - b2 = (a + b)(a - b)

@ : Home > Free Printable Worksheets > Math > a2 - b2

## a2 - b2 = (a + b) (a – b)

 Identity: a2 - b2 = (a + b) (a – b) How is this identity obtained? Let's see how. Taking RHS of the identity: (a + b) (a – b) Multiply as we do multiplication of two binomials or use F.O.I.L. method and we get: = a(a - b) + b(a - b) = a2 - ab + ab - b2 Solve like terms and we get: = a2 - b2 Hence, in this way we obtain the identity i.e. a2 - b2 = (a + b) (a – b) Following are a few applications to this identity. Example 1: Solve 9a2 - 4b2 Solution: This proceeds as: Given polynomial 9a2 - 4b2 represents the identity a2 - b2 = (a + b) (a – b) Where a = 3a and b = 2b On applying values of a and b on the identity a2 - b2 = (a + b) (a - b) and we get: (3a)2 - (2b)2 = (3a + 2b) (3a - 2b) Hence, 9a2 - 4b2 = (3a + 2b) (3a - 2b) Example 2: Solve (6m + 3n) (6m – 3n) Solution: This proceeds as: Given polynomial (6m + 3n) (6m – 3n) represents the identity a2 - b2 = (a + b) (a – b) Where a = 6m and b = 3n Now apply values of a and b on the identity i.e. a2 - b2 = (a + b) (a - b) and we get: (6m + 3n) (6m – 3n) = (6m)2 - (3n)2 Expand the exponential forms on the LHS and we get: = 36m2 - 9n2 Hence, (6m + 9n) (6m – 9n) = 36m2 - 81n2